Determinant factors of structural similarity at the regional level: evidence from Portugal - Crespo, N.; Fontoura, M. P. (Applied Econometrics and International Development, 2010)
There is scant evidence on the determinant factors of structural similarity between geographical spaces; moreover, it has been produced considering only the national level. The present study provides evidence on this topic at the regional level, based on the analysis of 275 Portuguese counties. The results obtained confirm the importance of several explanatory factors, suggesting that the structural similarity between Portuguese counties increases with geographical proximity, the existence of a shared boundary, the similarity of factor endowments in terms of physical and human capital and the similarity in terms of economic centrality and market dimension. Key words: productive structure, Portugal, structural similarity, factor endowments, economic geography